Modulation of whistle production related to training sessions in bottlenose dolphins (Tursiops truncatus) under human care. Issue 6 (24th October 2016) - Lopez Marulanda, Juliana; Adam, Olivier; Delfour, Fabienne
Abstract : Bottlenose dolphins are highly social cetaceans with an extensive sound production including clicks, burst‐pulsed sounds, and whistles. Some whistles, known as signature whistles, are individually specific. These acoustic signatures are commonly described as being emitted in contexts of stress during forced isolation and as group cohesion calls. Interactions between humans and captive dolphins is largely based on positive reinforcement conditioning within several training/feeding sessions per day. Vocal behavior of dolphins during these interactions might vary. To investigate this, we recorded 10 bottlenose dolphins of Parc Asterix dolphinarium (France) before, during and after 10 training sessions for a total duration of 7 hr and 32 min. We detected 3, 272 whistles with 2, 884 presenting a quality good enough to be categorized. We created a catalog of whistle types by visual categorization verified by five naive judges (Fleiss' Kappa Test). We then applied the SIGID method to identify the signatures whistles present in our recordings. We found 279 whistles belonging to one of the four identified signature whistle types. The remaining 2, 605 were classified as non‐signature whistles. The non‐signature whistles emission rate was higher during and after the training sessions than before. Emission rate of three signature whistles types significantly increased afterwards as compared to before the training sessions. We suggest that dolphins use their signature whistles when they return to their intraspecific social interactions succeeding scheduled and human‐organized training sessions. More observations are needed to make conclusions about the function of signature whistles in relation to training sessions. Zoo Biol. 35:495–504, 2016. © 2016 Wiley Periodicals, Inc.